TOXICITY PREDICTION, MOLECULAR DOCKING, MOLECULAR DYNAMICS SIMULATION MONASCUS SP. PIGMENT AS ANTIVIRAL HUMAN IMMUNODEFICIENCY VIRUS (HIV) CANDIDATE - Susilawati, Anissa
Monascus sp. pigment is a pigment that produced by Monascus sp. belonging to the azaphilone group. This pigment is being developed because of its biological activity in providing broad benefits in drug development, including being antihypercholesterolemia, antidiabetic, antimicrobial, anti-colon cancer, anti-breast cancer, antiviral HCV and others. Currently, HIV is still the first case of infection for which treatment still has a toxic effect. Therefore, the purpose of this study was to examine the potential of Monascus sp. as an HIV antiviral. Receptors and enzymes used include: CCR5 (4MBS), Reverse Transcriptase (3V81), Integrase (6PUW) and Protease (6DH3) which are bound to drug compounds (Maroviroc, Nevirapine, Bictegravir and Darunavir). A total of 61 test compounds were modeled using ChemDraw 3D Professional 16.0 software and then geometric optimization was carried out using the 3-21G basis set DFT method using Gaussians 09 software. Physicochemical predictions were made using Lipinski's rule and toxicity predictions were made using pkCSM software. Molecular docking was performed using Autodock 4.2 and molecular dynamics simulation using GROMACS 2016.3. From the results of molecular docking, it was found that the compound Red Derivat 3 had a more negative energy binding than Nevirapine, the compound Red Derivat 2 had a more negative energy binding than Bictegravir and the compound Monankarin C had a more negative bond energy binding than Darunavir. From the molecular dynamics simulation results, Red Derivat 3 compound in Reverse Transcriptase (3V81) has a more negative energy binding than Nevirapine, but does not pass Lipinski's rule. Based on the results of this study, the compound Red Derivat 3 has the potential to be investigated further regarding its activity as candidate for the Human Immunodeficiency Virus (HIV) antiviral with a drug delivery route other than oral.